A qualitative study of stakeholder views of the conditions for and outcomes of successful clinical networks - McInnes Elizabeth; Middleton Sandy; Gardner Glenn; Haines Mary; Haertsch Maggie; Paul Christine L; Castaldi Peter (BMC, 2012)
Abstract Background Clinical networks have been established to improve health outcomes and processes of care by implementing a range of innovations and undertaking projects based on perceived local need. Limited research exists on the necessary conditions required to bring about successful network outcomes and what characterises network success from the perspective of those involved in network initiatives. This qualitative study identified stakeholder views on i) the conditions for effective clinical networks; and ii) desirable outcomes of successful clinical networks. Methods Twenty-seven participants were interviewed using face-to-face audio-recorded semi-structured interviews. Transcribed data were coded and analysed to generate themes relating to the study aims. Results Five key factors represented as sub-themes were identified as important conditions for the establishment of successful clinical networks under the main theme of effective network structure, organisation and governance. These were: building relationships; effective leadership; strategic evidence-based workplans; adequate resources; and ability to implement and evaluate network initiatives. Two major themes encapsulated views on desirable outcomes of successful clinical networks: connecting and engaging which represented the outcomes of interdisciplinary and consumer collaboration and, partnerships with state health and local health services, and changing the landscape of care, which represented the importance of outcomes associated with improving services, care and patient health outcomes and implementing evidence-based practice. Conclusions This study provides new knowledge on the conditions needed to establish successful clinical networks and on desirable outcomes arising from network projects and initiatives that are considered to be valuable by those working in or associated with clinical networks. This provides health services with information on what needs to be in place for successful networks and on the types of outcomes that can be considered for assessing network effectiveness.